Commercial aquaponics approaching the European market: to consumers’ perceptions of aquaponics products in Europe - Milicic, V. (2018)
The first commercial aquaponics companies are starting up in Europe. The main focus has been on solving technology issues and optimizing production. However, increasing attention is now being paid to certification and regulations linked to aquaponics, as well as the marketing of products and services. The paper presents the results of a study whose main aim was to estimate consumers’ knowledge about aquaponics and their acceptance of aquaponics products in different European regions. An on-line questionnaire was administered to the general public through the aquaponics network of Food and Agriculture COST (European Cooperation in Science and Technology) Action FA1305 “The EU Aquaponics Hub—Realising Sustainable Integrated Fish and Vegetable Production for the EU” in 16 European countries. The methodology includes univariate and multivariate statistical techniques. The results show that, on average, attitudes towards aquaponics were positive, showing no significant differences between those who already knew about aquaponics and those who only heard about it through the survey. More than 50% of respondents had never heard of aquaponics, whilst more than 70% had already heard of hydroponics. No more than 17% of respondents were willing to pay more for aquaponically produced products and no more than 40% more when compared to the price of products from conventional farming. The results confirm three different clusters of potential consumers of aquaponics products. They also suggest an urgent need for implementing integrated and holistic approaches involving all stakeholders in aquaponics, in order to define a marketing plan and efficient communication strategies. This COST action, other projects and public decision makers must invest in educating consumers about aquaponics through the organization of guided tours, thematic workshops and tastings of aquaponics products in order to raise their awareness about this new technology. It is absolutely urgent that public decision makers, in cooperation with aquaponics stakeholders, address the main institutional constraints, namely the introduction of aquaponics as an economic activity and the organic certification of aquaponics products.